Utilization of Sewage Sludge Using Multiple Thermal Conversion Processes - Lin, Ta-Hui; Fauzy, Annas; Chen, Guan-bang; Wu, Fang-Hsien (Teknomekanik, 2021)
Sewage sludge is a usual waste from urban areas that can be utilized in many renewable energy sources. In this study, we examine the sewage sludge utilization using pyrolysis process to produce pyrolytic oil using Taguchi methods, combustion characteristic of sludge pyrolytic oil (SPO) blend with heavy fuel oil (HFO), and co-gasification of sewage sludge with CO2/steam as the gasification medium using Taguchi methods. The best-operating conditions for the pyrolysis of sewage sludge are a heating rate of 10oC/min, temperature of 450oC, the residence time of 60 min, and N2 flow rate of 700 mL/min. Under these conditions, the obtained pyrolytic oil yield is very close to the result from the Taguchi method calculation. In the combustion characteristic of sludge pyrolytic oil (SPO) blend with heavy fuel oil (HFO), a higher SPO in the fuel blend enhances the occurrence of micro-explosion and reduces the size of the residual. Higher SPO content in the fuel blend increases the combustion rate and increases the ignition delay due to moisture evaporation. In the co-gasification of sewage sludge and palm kernel shell optimization using Taguchi method, the best operational condition for maximum H2/ CO syngas ratio reaches at the gasification temperature of 900 C, a blending ratio of 30%, a CO2/(CO2+H2O) ratio of 70%, and a catalyst addition of 20% bed material mass. The best operating condition for maximum concentration of H2 reach with gasification temperature of 800 C, a blending ratio of 40%, a CO2/(CO2+H2O) ratio of 70%, and a 15% catalyst addition of bed material mass. The CO2/(CO2+H2O) ratio is the most important parameter among both case.